Downregulation of eEF1A/EFT3-4 Enhances Dopaminergic Neurodegeneration After 6-OHDA Exposure in C. elegans Model - Chalorak, Pawanrat; Dharmasaroja, Permphan; Meemon, Krai (Frontiers in Neuroscience, 2020)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by the aggregation of α-synuclein protein and selective death of dopaminergic (DA) neurons in the substantia nigra of the midbrain. Although molecular pathogenesis of PD is not completely understood, a recent study has reported that eukaryotic elongation translation factor 1A (eEF1A) declined in the PD-affected brain. Therefore, the roles of eEF1A1 and eEF1A2 in the prevention of DA neuronal cell death in PD are aimed to be investigated. Herein, by using Caenorhabditis elegans as PD model we investigated the role of eft-3/eft-4, the worm homolog of eEF1A1/eEF1A2, on 6-hydroxydopamine (6-OHDA)-induced DA neuron degeneration. Our results demonstrated that the expressions of eft-3 and eft-4 were decreased in the 6-OHDA-induced worms. RNA interference (RNAi) of eft-3 and eft-4 resulted in dramatic exacerbation of DA neurodegeneration induced by 6-OHDA, as well as aggravated the food-sensing behavior, ethanol avoidance, and decreased lifespan when compared with only 6-OHDA-induced worms. Moreover, downregulation of eft-3/4 in 6-OHDA-induced worms suppressed the expression of the anti-apoptotic genes, including PI3K/age-1, PDK-1/pdk-1, mTOR/let-363, and AKT-1,2/akt-1,2, promoting the expression of apoptotic genes such as BH3/egl-1 and Caspase-9/ced-3. Collectively, these findings indicate that eEF1A plays an important role in the 6-OHDA-induced neurodegeneration through the PI3K/Akt/mTOR pathway and that eEF1A isoforms may be a novel and effective pro-survival factor in protective DA neurons against toxin-induced neuronal death.